2013
DOI: 10.1021/ol4005917
|View full text |Cite
|
Sign up to set email alerts
|

Facile Cu(I)-Catalyzed Oxidative Coupling of Anilines to Azo Compounds and Hydrazines with Diaziridinone under Mild Conditions

Abstract: A mild and highly efficient Cu(I)-catalyzed oxidative coupling of anilines is described. Various primary and secondary anilines can be efficiently coupled under mild conditions to the corresponding azo compounds and hydrazines in high yields. This method provides a direct and practical access to these compounds, and is also amenable to gram scale with no special precautions to exclude air or moisture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 133 publications
0
44
1
Order By: Relevance
“…Unfortunately, the benzylic position of the bridge is deprotonated under these conditions, leading to a plethora of side products. Formation of the N=N double bond by oxidation of diamines [ 21 23 ] cannot be applied either, because the sulfur bridge is oxidized to the sulfoxide or sulfone. Hence, neither reductive nor oxidative conditions are compatible with the –CH 2 -S– bridge.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the benzylic position of the bridge is deprotonated under these conditions, leading to a plethora of side products. Formation of the N=N double bond by oxidation of diamines [ 21 23 ] cannot be applied either, because the sulfur bridge is oxidized to the sulfoxide or sulfone. Hence, neither reductive nor oxidative conditions are compatible with the –CH 2 -S– bridge.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that di- tert -butyldiaziridinone ( 1 ) can also be used for the oxidation of alcohols 22 and oxidative coupling of anilines 23 using Cu(I) as catalyst. During our studies on the oxidation of alcohols, 1,6-diphenylhexa-2,4-diyne-1,6-dione ( 4a ) instead of 1-phenylpropynone ( 3a ) was obtained in 31% yield under the reaction conditions when propargyl alcohol 2 was used as substrate (Scheme 1).…”
mentioning
confidence: 99%
“…In recent years, the copper-catalyzed oxidative dimerization of aniline derivatives brought new opportunities for the synthesis of azobenzenes. [71][72][73][74][75] Typically, copper(I) halides were used as catalytic copper source in the presence of different bases, ligands, and oxidants. As base, pyridine proved to be the most efficient, and the oxidative conditions were achieved by the application of oxidizing agents, oxygen or air atmosphere.…”
Section: Synthetic Strategies Towards Aromatic Azo Compoundsmentioning
confidence: 99%
“…To avoid precipitation and blockage in the reactor channels, the applied concentration of the starting material proved to be 0.5 M. According to literature data, due to the typical temperature range 60-100 °C, the reaction media are mainly nonvolatile solvents, such as toluene [69,72,75] and MeCN. [69,[71][72][73][74][75] As a consequence of the restrictive batch technology, the application of low-boiling solvents is still unexplored in this transformation. Thus we versions were registered with the value of 12% and 4% respectively ( Table 5 entries 1 and 2).…”
Section: Scheme 9 Model Reaction For Optimization Of the Copper-catamentioning
confidence: 99%
See 1 more Smart Citation